Estimasi Beban Emisi Kendaraan Bermotor dan Analisis Faktor Pengaruhnya di Lingkungan Kampus Politeknik Pertanian Negeri Samarinda - Denny Maruf, Shalehudin; Rajab, Arini; Azwari, Fachruddin; Alkas, Taufiq Rinda; Triyono, Joko (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2026)
The growth of motor vehicles, particularly motorcycles, significantly contributes to air pollution, including in campus environments with high mobility. This study aims to analyze the relationship between vehicle age and mileage on exhaust emissions and to estimate the emission load of motor vehicles in Politeknik Pertanian Negeri Samarinda. A quantitative approach was applied through direct measurement of exhaust emissions from 50 motorcycles using a gas analyzer, followed by correlation analysis and emission load estimation using the Tier 2 approach based on Vehicle Kilometer Traveled (VKT). The results indicate that vehicle age has a very weak correlation with HC (r = 0.11) and CO (r = 0.12), while mileage shows a stronger correlation with HC (r = 0.39) and CO (r = 0.31). The estimated emission load is 10.30 kg/day for CO and 4.35 kg/day for HC. Although the travel distance is relatively short, the high number of vehicles leads to a significant accumulation of emissions. These findings indicate that, at the campus scale, the number of vehicles and mobility intensity are the dominant factors influencing emission loads. Therefore, internal campus transportation management is necessary to reduce emissions.